Archetypes of Teaching: Tethers in the Wind or Flashlights in the Dark? - John M. Dirkx; Dan Pratt; Edward Taylor (Adult Education Research Conference, 2002)
A small but growing body of research focuses attention on how teacher assumptions, beliefs, and theories inform and shape teachers’ actions within learning settings in adult and higher education. In this article, however, we suggest that teachers’ rational conceptions and structuring of their work are grounded in emotional issues that cut across cultural and historical contexts. These emotional structures are manifest in familiar images, reflecting an underlying archetypal nature to teaching.